A A SPEECH ACTS ANALYSIS OF TEACHERS' TALK IN ENGLISH FOR YOUNG LEARNERS CLASS - Karim, Nur Aisyah; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2023)
The aims of this research are to know the types of speech acts performed by English teachers when talking in the classroom and the teacher's reason for using the most specific kind of speech act. This research used a qualitative research design because the classroom activity became the data source. The participant of this research was 1 English teacher in English Club at SDIT Cordova. The data was collected through observation and interviews. The data was analyzed through four steps: classifications, data reduction, data display, and verification/conclusion drawing. According to the findings, the data showed 71% of the talk used directive. Teachers utilize directive types because they are interested in their students' competencies, whether or not their teachings have been comprehended, and whether or not students can recognize examples of the material they have been given. Meanwhile, the opposite result displayed in the data is declarative. Moreover, the finding also showed that the Teacher produced other speech acts such as assertive, commissive, and expressive. The teacher uses speech acts to ensure that the teaching and learning process runs smoothly and the material is well received by the students.